Syllable Structure and Nasalization Change in Makassar Language - Nurul Khasanah; Agus Subiyanto (Bina Nusantara University, 2020)
The research discussed two points of phonological process related to changes in the syllable structure and nasalization in Makassar language. The data were analyzed by distributional and identity methods using a direct sorting technique. The affixes that form the verb of Makassar language were sorted by the type of prefix. Researchers also used the direct sorting form of phonetic articulation. The steps of analyzing data used Sudaryanto’s theory. The affixes that discussed in the research were /ak-/ and /an-/. The phonological process was described by using the theory of generative phonology of Schane. The result shows the types of sound and syllabic changing. They are; (a) sound changing of [ak-] becomes [ʔ] named glottalization; (b) sounds changing of [ak-] becomes nasalization; (c) gemination of [ak-] and [an-]; (d) sound changing of / an-/ becomes [aŋ-]; (e) sound release and insertion of prefix /an-/; (f) sound change and nasalization. The distinctive feature is used to explain the rules of the phonological process.